THE IMPACT OF GOVERNANCE POLICIES ON THE PRICE OF FRESH FRUIT BUNCHES (FFB) OF OIL PALM IN INDONESIA - Riyadi Mustofa; Gulat Medali Emas Manurung; Riati Bakce; Roslida binti Saat (Yayasan Education and Social Center, 2026)
As a strategic commodity, oil palm attends as a major supplier of raw materials to worldwide industries and makes a substantial contribution to national income and foreign exchange earnings. The upstream and downstream segments of this industry generate significant multiplier effects across both the macroeconomic and microeconomic sectors while improving the welfare of smallholders and surrounding communities. However, global market dynamics frequently create uncertainty in the prices of Fresh Fruit Bunches (FFB). This study aims to evaluate the sustainability of smallholder oil palm plantations based on FFB price trends over the nine most recent pricing periods and to determine the socio-economic impacts and the sensitivity of the government's proposed single-gate export policy for strategic commodities on FFB prices among scheme and independent smallholders. The study employs the Ordinary Least Squares method to examine price trends. The findings indicate that FFB prices for both scheme and independent smallholders are highly vulnerable to changes in government policies. The price trend for scheme smallholders is represented by the linear equation (Y = 3,465.85 - 338.89X), whereas the price trend for independent smallholders is represented by the equation (Y = 3,394.11 - 36.42X).